Novel insights into the aetiology of granulomatosis with polyangiitis—a case–control study using the Clinical Practice Research Datalink - Pearce, Fiona A.; Lanyon, Peter C.; Watts, Richard A.; Grainge, Matthew J.; Abhishek, Abhishek; Hubbard, Richard B. (Oxford University Press, 2018)
Objectives